Analysis and Design of High-Energy-Efficiency Amplifiers for Delta-Sigma Modulators - Jinze Lai; Yuxuan Lin; Gumeng Zhao; Lijie Huang; Cong Wei; Rongshan Wei; Wei Hu (Active and Passive Electronic Components)
This study presents a dynamic amplifier with high energy efficiency and high gain suitable for a delta-sigma modulator based on the floating-inverter amplifier (FIA), in-depth analysis of the existing FIA and its improved structure, and simulation verification. Compared with other FIA structures, the proposed amplifier has a better compromise in terms of power consumption and stability, which was designed and simulated using the SMIC 180 nm CMOS technology. Under a 1.2 V power supply, the closed-loop direct current (DC) gain and the output swing were about 104 dB and ±380 mV, respectively, and the input-referred in-band noise was about −100 dB with the chopper circuit.